Pengaruh Edukasi dan Terapi Kompres Jahe Merah dalam Mengatasi Nyeri Kronis dengan Gout Athritis: Serly Wahyuni, Emilia, Muhammad Junaid Farrukh - Serly Wahyuni; Emilia Emilia; Muhammad Junaid Farrukh (STIKes Persada Husada Indonesia, 2026)
Gout arthritis is a condition that can interfere with a person's daily activities. Individuals with this condition will experience joint pain during movement, swelling, stiffness in the fingers when moved, and eventually, the person may become unable to carry out normal activities. The World Health Organization (WHO) reported that 34.2% of people worldwide experienced gout in 2020.Pain is an unpleasant sensory and emotional experience resulting from tissue damage and is subjective in nature. Chronic pain is constant or intermittent pain that persists over a period of time. Health education is a planned and systematic learning process aimed at increasing knowledge, a wareness, and skills. This study is an intervention-type research, in which the researcher conducts actions or treatments (interventions) on subjects to observe the impact. The participants involved were two clients or two families (two cases) with the same nursing problem and medical diagnosis, namely clients experiencing chronic pain due to gout. The assessment was carried out from May 12 to 28, 2025. From the assessment results, Ny. Sn had a uric acid level of 8.0 mg/dL and Ny. Sy had 8.7 mg/dL. The nursing diagnosis identified based on problem screening was: Chronic Pain Related to the Family’s Inability to Care for Sick Family Members, with a score of 5. The planned interventions were General Objective and Specific Objectives 1–5, with the expectation that the family would be able to recognize the problem, make decisions, provide care, modify the environment and diet, and utilize health care facilities. During the evaluation stage, the planned actions were carried out for both clients and the problems were resolved.